Distance from Bloch-Type Functions to the Analytic Space F(p,q,s) - Cheng Yuan; Cezhong Tong (Abstract and Applied Analysis)
The analytic space F(p,q,s) can be embedded into a Bloch-type space. We establish a distance formula from Bloch-type functions to F(p,q,s), which generalizes the distance formula from Bloch functions to BMOA by Peter Jones, and to F(p,p-2,s) by Zhao.